1974
DOI: 10.1007/bf00388395
|View full text |Cite
|
Sign up to set email alerts
|

The roles of auxin and gibberellin in reversing radiation inhibition of hypocotyl lengthening

Abstract: Inhibition of hypocotyl lengthening in Lupinus albus seedlings mediated through the high energy reaction was not reversed by 5 authentic gibberellins nor by extracted lupin "gibberellin-like" compounds. However, inhibition by continuous light was largely overcome by applying IAA (indole-3-acetic acid) to intact seedlings. In contrast, inhibition of lengthening mediated through phytochrome in its low energy mode was reversed by gibberellin. It is concluded that light antagonises hormone-regulated growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

1976
1976
1989
1989

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…In some cases light inhibition of hypocotyl or mesocotyl extension can be overcome by IAA (ACTON andMURRAY 1974, VANDERHOEF andBRIGGS 1977). This is the case in lettuce hypocotyls, where the data indicate a correlation between light-induced growth inhibition and both reduced auxin content and apparent reduced sensitivity of the cells to auxin.…”
Section: Effects On Auxinmentioning
confidence: 73%
See 3 more Smart Citations
“…In some cases light inhibition of hypocotyl or mesocotyl extension can be overcome by IAA (ACTON andMURRAY 1974, VANDERHOEF andBRIGGS 1977). This is the case in lettuce hypocotyls, where the data indicate a correlation between light-induced growth inhibition and both reduced auxin content and apparent reduced sensitivity of the cells to auxin.…”
Section: Effects On Auxinmentioning
confidence: 73%
“…The inhibitory effect of white light on hypocotyl extension seems not to be due simply to a reduction in GA. JONES and LANG (1968) found no difference in the GA content of light-grown and dark-grown pea stem tissue while in Lupinus albus, the content of free GA was found to increase during exposure to white light (ACTON and MURRAY 1974). This indicates that white light inhibition of elongation may be more closely related to a photoinduced decrease in the ability of the tissue to respond to GA (JONES and LANG 1968, MUSGRAVE and KENDE 1970, ACTON and MURRAY 1974 than to changes in GA content.…”
Section: Effects On Auxinmentioning
confidence: 86%
See 2 more Smart Citations
“…Thus GA3 affected both the mechanical (viscoelastic) and biochemical (chemorheological) properties of the cell walls of light-grown cucumber. The previous hypothesis, that GA3 stimulates cucumber hypocotyl growth by increasing osmotic pressure and cell turgor, is contradicted by our results.GA3 can reverse the inhibition of stem elongation caused by light in many plant species (1,12,17,18,21,23,24). The mechanism by which GA3 enhances the rate of elongation has been investigated by several groups, many of whom have concluded that GA3 acts on cell wall mechanical properties to increase growth (2,13,15,18,20).…”
mentioning
confidence: 99%